Analisis Penegakan Hukum Ekonomi Syariah Terhadap Jual Beli Minyak Goreng Semakin Meroket Di Masa Pandemi Covid-1 - Muslih; Andre Pebrian Perdana (STAI Al-Mas'udiyah, 2022)
Due to the current COVID-19 pandemic, there have been many increases in the prices of basic goods such as cooking oil. Indeed, Islam has provided a solution in overcoming the price increase. If the soaring price of basic necessities is caused by natural factors that cause a scarcity of an item, besides this, people are required to be patient. And in Islam it also obliges the state to overcome this scarcity by seeking supplies from other regions, even Islam forbids people who do not understand fiqh law (related to business) from doing business. In this study, the author uses a normative legal research method that relies on literature studies and the focus is on analyzing primary and secondary legal materials. Where primary legal materials are applicable legal regulations and legal cases, while secondary legal materials include legal opinions contained in legal books and journals.